Island‐wide aridity did not trigger recent megafaunal extinctions in Madagascar. Issue 8 (22nd June 2016) - Crowley, Brooke E.; Godfrey, Laurie R.; Bankoff, Richard J.; Perry, George H.; Culleton, Brendan J.; Kennett, Douglas J.; Sutherland, Michael R.; Samonds, Karen E.; Burney, David A.
Abstract : Researchers are divided about the relative importance of people versus climate in triggering the Late Holocene extinctions of the endemic large‐bodied fauna on the island of Madagascar. Specifically, a dramatic and synchronous decline in arboreal pollen and increase in grass pollen ca 1000 yr ago has been alternatively interpreted as evidence for aridification, increased human activity, or both. As aridification and anthropogenic deforestation can have similar effects on vegetation, resolving which of these factors (if either) led to the demise of the megafauna on Madagascar has remained a challenge. We use stable nitrogen isotope (δ 15 N) values from radiocarbon‐dated subfossil vertebrates to disentangle the relative importance of natural and human‐induced changes. If increasing aridity were responsible for megafaunal decline, then we would expect an island‐wide increase in δ 15 N values culminating in the highest values at the time of proposed maximum drought at ca 1000 yr ago. Alternatively, if climate were relatively stable and anthropogenic habitat alteration explains the palynological signal, then we would anticipate little or no change in habitat moisture, and no systematic, directional change in δ 15 N values over time. After accounting for the confounding influences of diet, geographic region, and coastal proximity, we find no change in δ 15 N values over the past 10 000 yr, and no support for a period of marked, geographically widespread aridification culminating 900–950 yr ago. Instead, increases in grasses at around that time may signal a transition in human land use to a more dedicated agro‐pastoralist lifestyle, when megafaunal populations were already in decline. Land use changes ca 1000 yr ago would have simply accelerated the inevitable loss of Madagascar's megafauna.